REDUCTION OF LOSSES IN RADIAL DISTRIBUTION LINES USING FUZZY LOGIC - DAUD, MOHD FARIZ (universiti teknologi petronas, 2005)
Distribution system provides the final link between the high voltage transmission system and the customers. Radial distribution system with a single circuit main feeder is popular because of simple design and generally low cost. The power loss in a distribution system is significantly high because of lower voltage hence high current and losses (I2R). Reduction of reactive power is beneficial to improve overall efficiency and reduce cost. This project is to analyze losses in radial distribution system and compensate the losses with an intelligent method using fuzzy logic. Fuzzy logic is used together with numerical approach to determine the suitable candidate node for capacitor placement at distribution load busbar to compensate losses in the line. This report will articulate the work that has been done by the author in the project for the purpose of fulfillment of the Final Year Project.